Role of Social Commerce Constructs and Social Presence as Moderator on Consumers' Buying Intentions During COVID-19 - Rashid, Rao Muhammad; Pitafi, Abdul Hameed; Qureshi, Muhammad Asif; Sharma, Anshuman (Frontiers in Psychology, 2022)
Social interactions through social commerce platforms empower consumers to share their personal experiences with others, but its role becomes more significant for societal protection during COVID-19. Numerous scholars have studied e-commerce extensively, but there is a lack of studies to identify social commerce characteristics to attract potential consumers during COVID-19. This study aims to examine the role of social commerce constructs by integrating social presence as a moderator in the model to explain consumers online shopping intentions in a Pakistani context, where lack of trust on the reliability and validity of comments from other consumers being considered the growing concern towards the success of social commerce. The quantitative data was collected from the respondents living in different cities of Pakistan. Most of the hypothesis supported and demonstrate the positive response from the Pakistani consumers having experience of shopping through social commerce platforms. The findings of this study will help scholars and managers to understand the attitude of Pakistani consumers.